Ketimpangan Diglosik dalam Peristiwa Tutur Masyarakat Multilingal Mesuji Raya Sumatera Selatan - Muslihah Muslihah; Muhammad Suryadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this research is to explain the linguistic situation in the form of diglossic inequality in speech events that occur in the Mesuji Raya. The method used in this research is descriptive qualitative. The stages in this study began with data collection conducted by observation, interview, and note taking techniques. The data in this study consisted of natural utterances used by the Javanese Mesuji Raya speech community. The next stage is the stage of data analysis carried out by the matching method. The results obtained after analyzing the data are Javanese and Indonesian language codes have the Javanese language of instruction in Mesuji Raya and the seat is of a high variety (T) and the low variance code (R), Javanese speakers in this region do not like to use Javanese language codes correctly, and Understand also Understanding the language given by the Javanese people in Mesuji Raya in the various manners is still low. Conclusion, the use of the low variance code (R) is also used as a means of code switching in high variance speech (T), this is caused by linguistic factors, namely the ability of utilization required by the speaker. Keywords: Diglosic Inequality, Multilingual Society, Mesuji Raya.